Performance of the phonatory deviation diagram in the evaluation of rough and breathy synthesized voices, - Lopes,Leonardo Wanderley (2018)
Abstract Introduction Voice disorders alter the sound signal in several ways, combining several types of vocal emission disturbances and noise. The phonatory deviation diagram is a two-dimensional chart that allows the evaluation of the vocal signal based on the combination of periodicity (jitter, shimmer, and correlation coefficient) and noise (Glottal to Noise Excitation) measurements. The use of synthesized signals, where one has a greater control and knowledge of the production conditions, may allow a better understanding of the physiological and acoustic mechanisms underlying the vocal emission and its main perceptual-auditory correlates regarding the intensity of the deviation and types of vocal quality. Objective To analyze the performance of the phonatory deviation diagram in the discrimination of the presence and degree of roughness and breathiness in synthesized voices. Methods 871 synthesized vocal signals were used corresponding to the vowel /ɛ/. The perceptual-auditory analysis of the degree of roughness and breathiness of the synthesized signals was performed using visual analogue scale. Subsequently, the signals were categorized regarding the presence/absence of these parameters based on the visual analogue scale cutoff values. Acoustic analysis was performed by assessing the distribution of vocal signals according to the phonatory deviation diagram area, quadrant, shape, and density. The equality of proportions and the chi-square tests were performed to compare the variables. Results Rough and breathy vocal signals were located predominantly outside the normal range and in the lower right quadrant of the phonatory deviation diagram. Voices with higher degrees of roughness and breathiness were located outside the area of normality in the lower right quadrant and had concentrated density. Conclusion The normality area and the phonatory deviation diagram quadrant can discriminate healthy voices from rough and breathy ones. Voices with higher degrees of roughness and breathiness are proportionally located outside the area of normality, in the lower right quadrant and with concentrated density.